2006
DOI: 10.4141/a05-081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pasture type (alfalfa vs. grass) on methane and carbon dioxide production by yearling beef heifers

Abstract: . 2006. Effect of pasture type (alfalfa vs. grass) on methane and carbon dioxide production by yearling beef heifers. Can. J. Anim. Sci. 86: [409][410][411][412][413][414][415][416][417][418]. The objective of this study was to determine effect of pasture type on methane and carbon dioxide production by heifers grazing alfalfa or grass pastures at three sites across western Canada. All pastures were intensively managed so that heifers had ad libitum access to new forage material each day, and pastures were bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 41 publications
4
53
1
5
Order By: Relevance
“…A lower methane production expressed as mL/g DM for red clover compared with perennial ryegrass was also noted, but methane production expressed relative to feed degradability was reversed (Navarro-Villa et al, 2011), which has been explained due to the greater degradability of ryegrass. Methane production expressed in terms of feed intake was also higher with alfalfa than with grass (Chaves et al, 2006). However in this study, methane production (per unit of DM incubated or degraded OM) potential was generally lower for cereal and grass forages than legume forages though fiber content was lower in berseem and cowpea than in grass forages, and degradability of legume forages was high.…”
Section: Degradability Of Feeds and Rumen Fermentationmentioning
confidence: 49%
“…A lower methane production expressed as mL/g DM for red clover compared with perennial ryegrass was also noted, but methane production expressed relative to feed degradability was reversed (Navarro-Villa et al, 2011), which has been explained due to the greater degradability of ryegrass. Methane production expressed in terms of feed intake was also higher with alfalfa than with grass (Chaves et al, 2006). However in this study, methane production (per unit of DM incubated or degraded OM) potential was generally lower for cereal and grass forages than legume forages though fiber content was lower in berseem and cowpea than in grass forages, and degradability of legume forages was high.…”
Section: Degradability Of Feeds and Rumen Fermentationmentioning
confidence: 49%
“…Boland et al (2013) using the SF 6 tracer gas technique recorded CH 4 emissions from dairy heifers grazing good quality temperate pastures of 0.35 to 0.4 g/kg BW. Similarly, Chaves et al (2006) observed values of between 0.3 and 0.45 g/kg BW for grazing heifers in the Canadian prairies, while data from the United Kingdom for perennial ryegrass indicated higher emissions of 0.59 g/kg BW (Hammond et al, 2014). Data collected under tropical conditions using the OPL range between 0.52 and 0.56 g/kg BW (McGinn et al, 2011;Tomkins et al, 2011;McGinn et al, 2015).…”
Section: Tomkins and Charmleymentioning
confidence: 93%
“…From day 8 to day 16, collected effluent was sampled at the time of feeding and processed for volatile fatty acid (VFA) and ammonia analysis as described by Wang et al (1998). Prior to gas measurement on days 8Á16, a 10-mL sample of gas was obtained from the septum of collection bags using a 26-gauge needle (Becton Dickinson, Franklin Lakes, NJ) and transferred to evacuated 6.8-mL exetainers (Labco Ltd., Wycombe, Bucks, UK) for later analysis of daily methane concentration (Chaves et al 2006;Fraser et al 2007). The 48-h feedbags removed from each fermenter were processed to determine apparent DM disappearance (DMD) from day 8 to the end of the experiment as described by Li et al (2013).…”
Section: Sampling and Analysismentioning
confidence: 99%